Perlindungan Hukum bagi Konsumen pada Perjanjian Baku Shopee Pinjam - A Rahman Kh K; Sunaryo Sunaryo; Ahmad Zazili (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid growth of financial technology, particularly peer-to-peer (P2P) lending, has introduced electronic standard-form agreements that often place consumers in a weaker bargaining position. Shopee Pinjam (SPinjam), an unsecured digital loan service provided through cooperation with a licensed fintech lender, applies a standard electronic contract that raises concerns regarding contractual fairness and consumer protection. This study examines the legal validity of the SPinjam standard agreement based on Article 1320 of the Indonesian Civil Code and analyzes the extent of legal protection afforded to consumers under Indonesian consumer protection law. This research employs a normative legal method using statutory and conceptual approaches. Legal materials consist of primary sources in the form of legislation, supported by secondary and tertiary legal materials, which are analyzed qualitatively through descriptive-analytical techniques. The findings indicate that the SPinjam standard agreement formally fulfills the legal requirements of a valid contract under Article 1320 of the Civil Code. However, substantively, several contractual clauses demonstrate an imbalance of rights and obligations, potentially disadvantaging consumers and conflicting with the principles of fairness and consumer protection as stipulated in the Consumer Protection Act. Therefore, although legally valid in form, the agreement requires substantive adjustment to ensure equitable legal protection for consumers in fintech lending practices.